Influence of the Handbook in the Colombian Economic Thought during the Twentieth Century - Mayor Mora, Alberto; Zambrano Escamilla, Carlos Humberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The use of textbooks in economics has been massive in its professionalization, affecting Colombian economic ideas. There were four stages during the twentieth century; the first one at the beginning of the century, in which prevailed the selftaught system in the French manuals, among teachers, politicians and businessmen from Bogota and Medellin. The second stage was characterized by the contact on the outside of some prominent economists with the original economic thought, which produced the beginning of the critique to the use of manuals. The third one came with the first Faculties of Economics, in the 1940s, when the French manual was replaced by the neoclassical Anglo-Saxon; and the last stage starts from 1980 with a coherent critique of handbook and begins the production of “Creole” texts, which offer pedagogical indications with Avant-garde theoretical thinking.